A pilot study of the UVA-photoprotective potential of dehydrosilybin, isosilybin, silychristin, and silydianin on human dermal fibroblasts - Rajnochová Svobodová, Alena; Gabrielová, Eva; Ulrichová, Jitka; Zálešák, Bohumil; Biedermann, David; Vostálová, Jitka (Archives of dermatological research, 2019)
The exposure of naked unprotected skin to solar radiation may result in numerous acute and chronic undesirable effects. Evidence suggests that silymarin, a standardized extract from Silybum marianum (L.) Gaertn. seeds, and its major component silybin suppress UVB-induced skin damage. Here, we aimed to investigate the UVA-protective effects of silymarin's less abundant flavonolignans, specifically isosilybin (ISB), silychristin (SC), silydianin (SD), and 2,3-dehydrosilybin (DHSB). Normal human dermal fibroblasts (NHDF) pre-treated for 1 h with flavonolignans were then exposed to UVA light using a solar simulator. Their effects on reactive oxygen species (ROS), carbonylated proteins and glutathione (GSH) level, caspase-3 activity, single-strand breaks' (SSBs) formation and protein level of matrix metalloproteinase-1 (MMP-1), heme oxygenase-1 (HO-1), and heat shock protein (HSP70) were evaluated. The most pronounced preventative potential was found for DHSB, a minor component of silymarin, and SC, the second most abundant flavonolignan in silymarin. They had significant effects on most of the studied parameters. Meanwhile, a photoprotective effect of SC was mostly found at double the concentration of DHSB. ISB and SD protected against GSH depletion, the generation of ROS, carbonylated proteins and SSBs, and caspase-3 activation, but had no significant effect on MMP-1, HO-1, or HSP70. In summary, DHSB and to a lesser extent other silymarin flavonolignans are potent UVA-protective compounds. However, due to the in vitro phototoxic potential of DHSB published elsewhere, further studies are needed to exclude phototoxicity for humans as well as to confirm our results on human skin ex vivo and in vivo.
Keywords: Silymarin; karbonylace proteinů; jednořetězcové zlomy DNA; fibroblasty; Caspase 3; kaspasa 3; Fibroblasts; hemoxygenasa-1; reaktivní formy kyslíku; proteiny tepelného šoku HSP70; HSP70 Heat-Shock Proteins; Matrix Metalloproteinase 1; matrixová metaloproteinasa 1; cytoprotekce; Protein Carbonylation; kůže; Cytoprotection; silymarin; Sunscreening Agents; přípravky chránící proti slunci; ultrafialové záření; Reactive Oxygen Species; glutathion; kultivované buňky; DNA Breaks, Single-Stranded; lidé; Skin; Humans; Ultraviolet Rays; Glutathione; Cells, Cultured; Heme Oxygenase-1